2010
DOI: 10.1186/1471-2164-11-359
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone-induced differential gene expression in mouse liver carrying wild type or a dimerization-defective glucocorticoid receptor

Abstract: BackgroundGlucocorticoids (GCs) control expression of a large number of genes via binding to the GC receptor (GR). Transcription may be regulated either by binding of the GR dimer to DNA regulatory elements or by protein-protein interactions of GR monomers with other transcription factors. Although the type of regulation for a number of individual target genes is known, the relative contribution of both mechanisms to the regulation of the entire transcriptional program remains elusive. To study the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
90
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 103 publications
10
90
1
Order By: Relevance
“…To test this in a more physiological setting, we compared the expression of genes regulated by a GR ligand in LPS-stimulated WT macrophages to that in GR dim macrophages. As shown in Figure 5D, ligand has a reduced ability to modulate induced and repressed genes in GR dim macrophages, consistent with earlier findings in liver (Frijters et al 2010). Collectively, the data suggest comparable functions for GR monomers and dimers in primary macrophages and liver.…”
Section: Gr Dim Partitions the Gr Cistrome Similarly In Primary Macrosupporting
confidence: 90%
See 1 more Smart Citation
“…To test this in a more physiological setting, we compared the expression of genes regulated by a GR ligand in LPS-stimulated WT macrophages to that in GR dim macrophages. As shown in Figure 5D, ligand has a reduced ability to modulate induced and repressed genes in GR dim macrophages, consistent with earlier findings in liver (Frijters et al 2010). Collectively, the data suggest comparable functions for GR monomers and dimers in primary macrophages and liver.…”
Section: Gr Dim Partitions the Gr Cistrome Similarly In Primary Macrosupporting
confidence: 90%
“…In agreement with the transactivation mechanism, GR dim mice show a reduced ability to activate transcription in the liver in response to exogenous ligands (Frijters et al 2010). However, later studies were inconsistent with expectations for transrepression by revealing that GR dim mice exhibit a diminished response to GC treatment in inflammatory paradigms such as TNF-induced inflammation (Vandevyver et al 2012), LPSand CLP-induced sepsis (Kleiman et al 2012;Silverman et al 2013), antigen-induced rheumatoid arthritis (Baschant et al 2011(Baschant et al , 2012, allergic contact dermatitis (Kleiman and Tuckermann 2007), and experimental autoimmune encephalomyelitis, a mouse model for multiple sclerosis (Schweingruber et al 2014).…”
supporting
confidence: 59%
“…Recently, ChIP sequencing studies revealed a GRE site in the promoter region of Mkp1 (35,36). Furthermore, it was shown that DEX treatment leading to Mkp1 induction in liver and in various other cell types is dependent on GR dimerization (37). This was confirmed by our ChIP results, which indicated that binding of GR to Mkp1 and subsequent Mkp1 induction required GR dimerization.…”
Section: (E and F)supporting
confidence: 79%
“…Instead, the dominant model for GRmediated repression has centered on repressive tethering interactions between monomeric GR and inflammatory transcription factors, leading to gene inactivation in association with histone deactylation (4,15,57). More recently, however, it has become clear that mutations in the GR dimerization domain do not completely abrogate gene induction by GR, nor do mice harboring the GR dimerization mutation exhibit normal antiinflammatory responses (19,32,54,61). Moreover, a number of GR-induced targets, such as DUSP1, have emerged as being crucial for GR-mediated inflammatory repression in many tissues, including ASM (31,49).…”
mentioning
confidence: 99%